Modeling vibronic spectra of linear aggregates in MATLAB - Kasetty, Pranav; Mishra, DIvij; Nagesh, Jayashree (ChemRxiv)
Molecular aggregates display a rich array of photophysical properties quite different from the isolated molecules that have applications in photovoltaics and display technology. Hence, understanding their absorption and emission spectra gives clues about packing and coherence properties, essential for energy transport. We attempt to calculate the steady-state spectra of linear aggregates. We approached this problem by following the vibronic excitonic framework discussed by Spano and co-workers [Hestand & Spano, Chem. Rev. 2018, 118, 7069-7163]. The framework allows us to incorporate the influence of nuclear relaxation energy through the one-particle and two-particle states. We also study the effects of local static disorder, finite temperature, and periodic boundary conditions. We implement the calculation of the photoluminescence and absorption spectra in the user-friendly language MATLAB in a manner that allows sequentially increasing the complexity of the model by considering more effects as needed. The calculated spectra have been validated by matching them with spectra produced by Spano et al. Hence, we have implemented a robust code that can model spectra from linear aggregates of any size and orientation, subject to computational limitations. We are currently using these codes to assign the steady state spectra and speculate the morphology of several types of thin films made of donor-acceptor dyes obtained by an experimental collaborator at SSCU; these dyes are being put forward for use for increasing the efficiency of photovoltaic cells through the multi-exciton generation mechanism of singlet fission. The high-level language implementation allows usage without a programming background as long as the theoretical model is understood.